Data processing in FTIR imaging of cells: Towards protein secondary structure imaging. Issue 1 (2010) - Goormaghtigh Goormaghtigh, Erik Erik; Derenne Derenne, Allison Allison; Bénard Bénard, Audrey Audrey; Gasper Gasper, Régis Régis; Raussens Raussens, Vincent Vincent
Abstract : Focal plane arrays provide a rapid method for infrared imaging of cells and tissues. Beside statistical analyses designed to classify image features, insight into the structure of the molecules present in the sample can be obtained. The paper presents a simple way to retrieve complete information on protein secondary structure from the thousands of spectra obtained by imaging. Human PC-3 prostate cancer cells were shown here to present cell-to-cell variations in protein secondary structure which might be related to the cell cycle. Intracellular variations are small but intercellular variations can be quite significant. This observation could yield unanticipated insight in cell population analysis. Furthermore, the results demonstrate the robustness of secondary structure determination on individual pixels at a sub-cellular scale.